2003
DOI: 10.1177/00238309030460020701
|View full text |Cite
|
Sign up to set email alerts
|

Infant Perception of Non-Native Consonant Contrasts that Adults Assimilate in Different Ways

Abstract: Numerous findings suggest that non-native speech perception undergoes dramatic changes before the infant's first birthday. Yet the nature and cause of these changes remain uncertain. We evaluated the predictions of several theoretical accounts of developmental change in infants' perception of nonnative consonant contrasts. Experiment 1 assessed English-learning infants' discrimination of three isiZulu distinctions that American adults had categorized and discriminated quite differently, consistent with the Per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
174
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(189 citation statements)
references
References 76 publications
11
174
2
Order By: Relevance
“…Surprisingly, there are very few such data, and some of the data have been collected to examine perception of non-native sounds by children and adults outside the region. Best and McRoberts (2003) found that English-exposed infants and adults were able to distinguish Zulu clicks, but that adults were not able to distinguish non-native nonclick sounds, and concluded that the clicks are so different from native English phonemes that they are not assimilated to English phonemes (while the other nonnative phonemes are assimilated), so that as infants and children grow older they do not lose the ability to distinguish the clicks.…”
Section: Acquisition Of Clicksmentioning
confidence: 99%
“…Surprisingly, there are very few such data, and some of the data have been collected to examine perception of non-native sounds by children and adults outside the region. Best and McRoberts (2003) found that English-exposed infants and adults were able to distinguish Zulu clicks, but that adults were not able to distinguish non-native nonclick sounds, and concluded that the clicks are so different from native English phonemes that they are not assimilated to English phonemes (while the other nonnative phonemes are assimilated), so that as infants and children grow older they do not lose the ability to distinguish the clicks.…”
Section: Acquisition Of Clicksmentioning
confidence: 99%
“…The transition from an early universal phonetic ability to language specific phonetic perception occurs between 6 and 12 mo of age, when nonnative phonetic perception declines (Werker and Tees 1984;Best and McRoberts 2003;Rivera-Gaxiola et al 2005b;Tsao et al 2006) and there is increased sophistication in the processing of native speech (Kuhl et al 1992). Work in my laboratory showed that at the same time that nonnative perception for consonants declines, native-language speech perception shows a significant increase.…”
Section: The Timing Of Infant Learningmentioning
confidence: 87%
“…Infants' speech perception skills show a dual change toward the end of the first year of life ( Figure 1). Not only does nonnative speech perception decline (Best and McRoberts 2003;Werker and Tees 1984), but, also, native-language speech perception skills show improvement, reflecting a facilitative effect of experience with native language Tsao, Liu, and Kuhl 2006). The mechanism underlying change during this sensitive period in development, and the relationship between the change in native and nonnative speech perception, is of theoretical interest.…”
Section: Early Phonetic Learningmentioning
confidence: 99%